REVIEW OF THE DEATH PENALTY AGAINST PERPETRATORS OF NARCOTICS CRIME BASED ON SOSIOLOGY OF LAW - Kristiyadi Kristiyadi (Jurnal Inovasi Penelitian, 2022)
This article discusses the pros and cons of public views regarding the implementation of criminal sanctions for narcotics criminals in Indonesia. The study will focus on differences in public opinion in responding to the execution of the death penalty for narcotics criminals and efforts to formulate effective criminal penalties for drug crimes. The study in writing this article is based on the sociology of law, especially the theory of behaviorism and the theory of justice. In the perspective of the sociology of law, a sentencing device should include two things, namely: first, it must accommodate the aspirations of the people who demand retaliation as a balance on the basis of the level of guilt of the perpetrator. Second, it must include the purpose of punishment, namely to maintain and maintain community unity. Thus, the law must represent the community's sense of justice. Therefore, the attitudes and actions of people who choose the death penalty for narcotics criminals can be justified even though in other places the death penalty is abolished.